EMERGENCE OF CONTACT FILMS DURING FRICTION. GEOTRIBOLOGICAL FILMS - Emilia ASSENOVA (Proceedings on Engineering Sciences, 2019)
Focusing on frictional surfaces contact interaction study, tribology comprises, beside the wellknown friction/wear problems, the research on the genesis, characteristics and functioning of the films formed by the interacting materials in the contact zone. Self-building films occur as natural formations in frictional pairs, such as the secondary protective films, the frictional films formed at the selective transfer during friction, and the geotribofilms between adjacent geological rock plates in the Earth’s crust. The paper focusses on the creation of geotribofilms, especially of the mica schist films acting as lubricating films in the shear zones of friction between rock plates. Specifics of geotribological processes and products are the wide extent of scales, which they cover, and the possibility for history time tracking of the entire development of the object.